HUBUNGAN KEKUATAN OTOT PERUT DAN POWER OTOT TUNGKAI TERHADAP KETEPATAN LONG PASSING PEMAIN SEKOLAH SEPAK BOLA (SSB) PESAWAT PUTRA KU-14 KABUPATEN JOMBANG - Rahman, Muhammad Rafi'i Azizul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between abdominal muscle strength and leg muscle strength with the accuracy of long passing in 14-year-old players of Pesawat Putra Football School (SSB) in Jombang Regency. The method applied is a quantitative descriptive approach aimed at describing and assessing the connection between the variables of abdominal muscle strength, leg muscle strength, and long passing accuracy of the players using a correlational study design. There were 21 players who participated in this study, selected purposively. The tools used to collect data consisted of a 30-second sit-up test to assess abdominal muscle strength, a standing long jump test to measure leg muscle strength, and a long passing accuracy test to evaluate technical ability. The results of the correlation analysis showed a significant relationship between abdominal muscle strength and long passing accuracy (r = 0.790; p = 0.000), and also between Leg muscle strength is correlated with long passing accuracy (r = 0.577; p = 0.024). In addition, the multiple correlation test yielded a significant value of 0.003, indicating a meaningful relationship between the two variables of muscle strength and long passing accuracy. Thus, it can be concluded that abdominal and leg muscle strength significantly contribute to improving long passing accuracy among SSB Pesawat Putra KU-14 players in Jombang Regency.